Aphonia with Unknown Etiology: A Case Report - de Castro Guimaraes, Valeriana; Siqueira, Valeriana Humberto; da Silva Castro, Victor Labres; Barbosa, Maria Alves; Porto, Celmo Celeno (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction The conversion aphonia is defined as the total loss of voice, is a rare disease that often affects women. The diagnosis is clinical, because there are no changes in the laryngeal structures.Objective To describe a case of conversion aphonia, seen in a public hospital in the Midwest of Brazil.Case Report Patient 32 years old female, complaining of hoarseness for two days without other apparent symptoms. The examinations revealed no changes in the laryngeal structures and/or extra laryngeal. Stages of care have been described since the initial consultation to the recovery of the patient.Final Comments It is important to consider the psycho-emotional aspects involving patients with voice disorders since they may cause or modify the symptoms and affect the prognosis.
Keywords: aphonia; hoarseness; laryngeal diseases; stress; voice